On Demand Scoring System to Enhance Collaborative Learning Experiences in Mobile Learning - Arifin, Ifik; Wibawa, Basuki (International Journal of Psychosocial Rehabilitation, 2020)
How do you know if your students have truly learned what you set out to teach? This system is built around a class or remote class to assist the instructor and the students to control the result of their performance in real time. This application was designed with research and development in mind as a special tool for knowing the progress of learning in a collaborative environment. The results and findings will show not only increasing performance and motivation of the students, but also the instructor’s awareness about the strengths and weaknesses of actual session and class performance, and he or she can make adjustments for the next sessions accordingly to improve learning experiences.